Application of a novel method for soil aggregate stability measurement by laser granulometry with sonication. (21st January 2013) - Rawlins, B. G.; Wragg, J.; Lark, R. M.
<x xml:space="preserve">Abstract</x> Aggregate stability is an important physical indicator of soil quality, and so methods are required to measure it rapidly and cost‐effectively so that sufficient data can be collected to detect change with adequate statistical power. The standard methods to measure water‐stable aggregates (WSA) in soil involve sieving, but these have limitations that could be overcome if the aggregates were measured with a laser granulometer (LG) instrument. We present a novel method in which a LG is used to make two measurements of the continuous size distribution (<2000 µm) of a sample of aggregates. The first measurement is made on the WSA after these have been added to circulating water (initial air‐dried aggregate size range 1000–2000 µm). The second measurement is made on the disaggregated material (DM) after the circulating aggregates have been disrupted with ultrasound (sonication). We then compute the difference between the mean weight diameters (MWD) of these two size distributions; we refer to this value as the disaggregation reduction (DR; µm). Soils with more stable aggregates, which are resistant to both slaking and mechanical breakdown by the hydrodynamic forces during circulation, have larger values of DR. We applied this method to six and ten sub‐samples, respectively, of soil aggregates (each ca. 0.3 g) from bulk soil material from two contrasting soil types from England, both under conventional tillage (CT). The mean DR values were, respectively, 178 and 30 µm, with coefficients of variation of 12.1 and 19% suggesting the DR value is reproducible for the small mass of soil used. We attribute the larger DR values to the greater abundance of micaceous clay minerals in one of the soils. The DR values computed for each Blackwater Drain (BD) sample after removal of organic matter (with hydrogen peroxide) were comparable to those subject to sonication suggesting that most of the aggregate structure is removed by sonication. We used aggregates (1000–2000 µm) from soil samples collected at 30 locations under CT (median soil organic carbon (SOC) = 1.4%) across two types of parent material in the Blackwater drain sub‐catchments of the Wensum catchment (Norfolk, UK). These soils had no coarse WSA, so we rescaled the size distributions to estimate DR for particle diameters <500 µm. Dithionite‐extractable iron concentration, plus a minor contribution from parent material class, accounted for 64% of the variation in rescaled DR highlighting the importance of crystalline iron oxyhydroxides for aggregate stability in this region where long‐term arable production has reduced top‐soil SOC concentrations. We discuss how this technique could be developed to monitor aggregate stability as a soil physical indicator.